2012
DOI: 10.1093/cid/cis599
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Therapeutic Drug Monitoring on Safety and Efficacy of Voriconazole in Invasive Fungal Infections: A Randomized Controlled Trial

Abstract: NCT00890708.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
272
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(291 citation statements)
references
References 23 publications
7
272
1
4
Order By: Relevance
“…Voriconazole clearance averages 932 ml/min in ultrarapid metabolizers, 522 ml/min in extensive metabolizers, and 147 ml/min in poor metabolizers (194). Both CYP-2C19 genotyping and therapeutic drug monitoring have been suggested as approaches to guide therapy and control pharmacokinetic variability (195)(196)(197). The voriconazole half-life averages 7 to 14 h, depending on the genotype.…”
Section: Advances In Antifungal Therapy For Coccidioidomycosismentioning
confidence: 99%
“…Voriconazole clearance averages 932 ml/min in ultrarapid metabolizers, 522 ml/min in extensive metabolizers, and 147 ml/min in poor metabolizers (194). Both CYP-2C19 genotyping and therapeutic drug monitoring have been suggested as approaches to guide therapy and control pharmacokinetic variability (195)(196)(197). The voriconazole half-life averages 7 to 14 h, depending on the genotype.…”
Section: Advances In Antifungal Therapy For Coccidioidomycosismentioning
confidence: 99%
“…to medically important molds have been engineered at a cost of less-predictable pharmacokinetics (17). Voriconazole is an ideal candidate for therapeutic drug monitoring for the following reasons: (i) there are well-established drug exposure-effect and drug exposure-toxicity relationships (7,8,10); (ii) there is evidence that therapeutic drug monitoring may lead to improved therapeutic outcomes (8,18); and (iii) voriconazole exhibits significant interpatient variability with classical nonlinear pharmacokinetics (12). While therapeutic drug monitoring may be a desirable adjunct to the routine use of voriconazole, at this time there are no algorithms that can be used to adjust the regimen to attain predefined serum concentration targets in an optimally precise manner.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has reported mixed results concerning the association of voriconazole therapeutic drug monitoring. Park et al demonstrated that therapeutic drug monitoring reduces drug discontinuation due to adverse events and improves treatment response [28]; while Racil et al failed to establish improved outcomes with measured voriconazole concentrations [29]. The true magnitude of the utility of a standardized protocol for monitoring serum concentrations of nonweight based dosing for voriconazole as primary antifungal prophylaxis has yet to occur in a prospective, randomized trial and remains controversial.…”
Section: Discussionmentioning
confidence: 99%